INTEGRATIVE HOLISTIC EARLY CHILDHOOD DEVELOPMENT IN EARLY CHILDHOOD EDUCATION - Diana Setyaningsih; Nita Priyanti; Chandra Apriyansyah; Juariah; Nurul Puji Astuti; Eko Kurniasih; Frida Feka; Denni Yuniasih; Linda Ferawati (Universitas Panca Sakti Bekasi, 2023)
The purpose of this study was to determine the knowledge of teachers in Mertoyudan Magelang District about integrative holistic early childhood development. This research was motivated by the low understanding of teachers and education unit managers about the implementation of integrative holistic early childhood development programs. This research method uses quantitative methods with data collection tools in the form of observation, documentation, instruments, interviews and surveys. The object of this research is educators and heads of ECCE units in Mertoyudan Magelang District as many as 37 ECCE units. The time of this study is from March 1 to March 1. May 30, 2023. The results of this study showed that the understanding of integrative holistic early childhood development increased by 69.69% and the implementation of integrative holistic early childhood development in their respective institutions increased by 90.90%. The conclusion is that this socialization has a positive impact on early childhood education units in implementing integrative holistic early childhood development. From the conclusion of our research, researchers recommend to local governments to re-socialize the implementation of integrative holistic early childhood development programs in their regions.